INFORMACIÓN ACERCA DE LA PRESENCIA DE ALCORNOQUE ( Quercus suber L .) EN LA PROVINCIA DE GUADALAJARA - SERRADA HIERRO, R; García Viñas, J I (Investigación agraria. Sistemas y recursos forestales, 1999)
The paper gathers information on the so believed only natural presence of cork oak (Quercus suber L.) in the province of Guadalajara (Central Spain). It is the extremest eastern location of that species in the southern face of the Central Range of Mountains. The most important botanical, ecological and dasometrical aspects of the stand are described. An ecological homologation of the stand, based on Allué Andrade’s work, has also been carried out.
Keywords: Cork oak; Guadalajara; Quercus suber